Performance of a Salt-Accumulating Substitution Lime Render for Salt Laden Historic Masonry Walls - Ana Fragata; Rosário Veiga; Ana Velosa (Heritage, 2021)
Salt crystallization is one of the main decay processes in historic masonry mortars, and climate change can worsen the salt weathering effects on those materials as result of, e.g., more often rain falls, more intense solar radiation and sea level rise. In this paper, the effectiveness and durability of a substitution “ventilated render” system (a two-layer render, with base and outer layer and “vertical grooves” in the base layer) on a full-scale salt laden masonry wall to reproduce conditions that may be found in real cases was investigated. The crystallization at the interface between render layers and in vertical grooves and the effect of the porous structure on salt crystallization were thoroughly investigated. It was highlighted the reliability of the results of the salt crystallization testing procedure on a full-scale masonry wall to attest the efficiency and durability of the render system. Finally, it was proven that the ventilated render system with water repellent in the outer layer is durable and efficient enough to be used as a substitution render on salt laden historical masonries, acting as a salt accumulation render where salts preferably crystallize in, delaying the damage on the outer surface without introducing harmful effects in the masonry.